Measuring the Poverty of Productive Zakat Mustahik using the CIBEST Model - Masruroh, Nikmatul; Hari Sukarno; Yusril Firmansyah (EKONOMIKA SYARIAH : Journal of Economic Studies, 2024)
Abstract The productive Zakat is expected to contribute to alleviating poverty. The productive zakat model is a sustainable charity model and is not consumptive, so it can be expected to contribute to poverty alleviation. So, this research has some purposes thethe first is to explore the formula about the problem of productive zakat management carried out by BAZNAS; secondly, to analyze the impact of productive zakat on poverty alleviaton; and thirdly, to measure the poverty of mustahik productive zakat using the CIBEST model. The problem is solved using a mixed-method approach, namely qualitative with case study type and quantitative methods with descriptive statistics type. In this study, using qualitative research methods were used first, then continued using quantitative. This research took place in Probolinggo. Regency. The results of this study, first, the management of productive zakat by BAZNAS Probolinggo Regency uses the GAG ​​principle and uses the POAC management system. Second, productive zakat management has not had an impact on material poverty alleviation. Third, the poverty position of mustahik productive zakat using the CIBEST model, which is in quadrant II, it means that Mustahik has spiritual wealth and is materially poor.   Zakat produktif diharapkan bisa berkontribusi dalam mengentaskan kemiskinan. Model zakat produktif merupakan model charity yang berkelanjutan dan tidak bersifat konsumtif, sehingga bisa diharapkan bisa memberikan kontribusi pada pengentasan kemiskinan. Sehingga penelitian ini memiliki tujuan pertama mengeksplorasi tentang masalah pengelolaan zakat produktif yang dilaksanakan oleh BAZNAS, kedua, menganalisis dampak zakat produktif dalam pengentasan kemiskinan, ketiga mengukur kemiskinan mustahik zakat produktif dengan menggunakan model CIBEST. Masalah tersebut diselesaikan menggunakan pendekatan mix method, yaitu metode kualitatif dengan jenis studi kasus dan kuantitatif dengan jenis statistik deskriptif. Dalam penelitian ini menggunakan metode penelitian kualitatif terlebih dahulu, kemudian dilanjutkan menggunakan kuantitatif. Penelitian ini mengambil objek di Kabupaten Probolinggo. Hasil penelitian ini, pertama pengelolaan zakat produktif oleh BAZNAS Kabupaten Probolinggo menggunakan prinsip GAG dan menggunakan sistem manajemen POAC, kedua pengelolaan zakat produktif belum memiliki dampak bagi pengentasan kemiskinan secara materiil, ketiga posisi kemiskinan mustahik zakat produktif dengan model CIBEST, yaitu pada kuadran II artinya  mustahik memiliki kekayaan secara spiritual dan miskin secara material.